Korelasi Korupsi Politik Dengan Hukum dan Pemerintahan di Negara Modern (Telaah tentang Praktik Korupsi Politik dan Penanggulangannya) - Artidjo Alkostar (Fakultas Hukum Universitas Islam Indonesia, 2009)
Based on political corruption study and its correlation to the law and governance in modern countries, this research was aimed at identifying how political corruption correlates to socio-political, socio-economic, socio-cultural, socio-juridical and human right dimensions. To have social relevance to juridical analysis, this research also analyzed the strategy/policy to overcome the political corruption phenomena. Literary analysis and interviews with several experts having relevant scientific competence were the main basis for the research to compose this dissertation. The correlation between variables of the data obtained from the analysis of the content and the norm was described. The phenomena of legally prohibited corruptions were also compared. The political corruption analyzes in several modern countries, it is clear that political corruption has more extensive impact than corruption by the people without political position. The entity of political corruption is closely related with the power. Political corruption always attempts to maintain and extend the power abuse and the need for socio-political order requires equivalent control role in the implementation of the power. Political corruption correlates to human rights violation by governmental heads because political corruption is closely related to the desire to maintain and extend power.Key word: corelation, politic coruption, modern state